Understanding the Behaviour of Molecular Weight Fractions of Natural Organic Matter to Improve Water Treatment Processes - Kristiana, Ina; Allpike, Bradley; Joll, Cynthia; Heitz, Anna; Trolio, R. (IWA Publishing, 2010)
Water utilities have experienced increasing pressure to minimise the formation of disinfection by-products (DBPs), as reflected in the increasingly stringent regulations and guidelines for the concentrations of DBPs in drinking water. Understanding the disinfection characteristics and molecular weight (MW) distribution of natural organic matter (NOM) will assist in the optimisation of drinking water treatment processes to minimise the formation of DBPs. This study investigated the disinfection behaviour of MW fractions of NOM isolated from a Western Australian source water. The NOM was fractionated and separated using preparative size exclusion chromatography (SEC) and the fractions were chlorinated in the presence of bromide ion. The larger MW fractions of NOM were found to produce the highest concentrations of DBPs (trihalomethanes, haloacetic acids, haloacetonitriles, haloketones, and haloaldehydes), with the low MW fractions still producing significant amounts of these DBPs. The results also showed a trend of an increasing proportion of brominated DBPs with decreasing MW and aromatic character. Considering that the smaller MW fractions of NOM produce significant amounts of DBPs, with a higher relative contribution from brominated DBPs, water treatment processes need to be optimised for either bromide removal or the removal of aliphatic, small MW fractions of NOM, in order to meet DBP guidelines and regulations.